Serum sodium and potassium in asthmatic children - Omar S Ahmed; Amira M.M Hamed; Ismael A.R Kassem; Hamada K Fayed; Walid A Elmorsy (Al-Azhar Assiut Medical Journal, 2021)
Background Asthma is a disease outlined by its clinical, physiological, and pathological features. Airways inflammation and hyperreactivity of bronchial tissues were the most important manifestations of bronchial asthma. Aim The aim was to evaluate serum sodium and potassium levels in pediatric asthmatic patients and match these levels during and in between the attack and with healthy control children. Participants and methods This was a case–control study that was done on pediatric patients with asthma. The cases were children with confirmed asthma of an age group of 5–12 years old, and the age-matched controls were children without respiratory signs or symptoms. Serum sample for measuring absolute eosinophilic count, sodium, and potassium value was obtained. Results The mean values of serum sodium during the attack and in between the attack were 136.78±2.66 and 140.51±2.62 mmol/l, respectively, with significant difference (P<0.05). Both the mean values of serum sodium were found to be significantly lower than the mean value of the control (141.58±2.34 mmol/l). The mean values of serum potassium during the attacks and in between the attacks were 3.28±0.44 and 3.94±0.32 mmol/l, respectively (P<0.05). Both the mean values of serum sodium, i.e., during and in between, were found to be significantly lower than the mean value of the control (4.12±0.32 mmol/l). Hyponatremia was detected in 8 and 6% of the asthmatic patients during the attacks and in between attacks, whereas hypokalemia was detected in 56 and 9% of the asthmatic patients during the attacks and in between the attacks. Conclusion The study showed that asthmatic patients presented with hyponatremia and hypokalemia, and there is a significant difference between serum sodium and potassium levels during attacks and in between attacks and when compared with the control group.